Can all Italianisms in Serbo-Croatian be considered alike? The historical Influence and the long-lasting impact of Italian loanwords in the BCMS languages with a closer insight into the Croatian-Istrian case - Perpolli, Francesco (Mundus Slavicus I, 2025)
This article explores the extensive presence of Italian lexical borrowings—Italianisms—within the BCMS (Bosnian, Croatian, Montenegrin, and Serbian) language area, focusing on their historical development, structural features, and regional variations. The study begins with a broad overview of loanwords in BCMS, emphasizing their diverse origins, including Turkish, German, Hungarian, Greek, and French influences. The core analysis then examines Italianisms, classifying them into Venetianisms, Tuscanisms, cultural Italianisms, and new cultural Italianisms. Special attention is given to the spoken vernacular of Istria, a historically multilingual and multiethnic region where the interaction between Venetian dialects and local Slavic languages has resulted in unique linguistic phenomena. Drawing from documented examples and personal experience, the article highlights the complex assimilation process of Italianisms, questioning whether they can be treated as a homogeneous category. By analysing phonetic and morphological adaptations, as well as the socio-historical factors shaping linguistic influence, this study aims to contribute to a more nuanced understanding of lexical borrowing in the Balkans and the intricate legacy of Italian linguistic influence.